Rework in highway projects - Forcada, Nuria; Rusiñol, Gerard; MacArulla, Marcel; Love, Peter E. D. (Journal of Civil Engineering and Management, 2014)
There is limited systematic knowledge available about the dynamics of rework in highway projects, despite the fact that they frequently exceed budget and schedule by more than 10%. A case study of a Spanish highway project, which experienced a significant cost overrun as a result of rework, is examined and the causal factors that contributed to its occurrence are determined. Through observation and subsequent analysis of interviews and documentation a high degree of interdependency existed between perceived causes of rework. This resulted in the nomenclature of Project, Organization and People to be adopted and used to develop the rework generic systemic model. Scope changes, high complexity, poor skill levels and unexpected underground services were found to be the most significant causes of rework. The developed model provides managers with insights about the interdependencies and behaviour between key influencing variables in highway projects and can be used to stimulate learning and process improvements in future highway projects.